Peripheral injections of melanin-concentrating hormone receptor 1 antagonist S38151 decrease food intake and body weight in rodent obesity models - Della-Zuana, Odile; Audinot, Valerie; Levenez, Viviane; Ktorza, Alain; Presse, Françoise; Nahon, Jean-Louis; Boutin, Jean A. (Frontiers in Endocrinology, 2012)
The compound S38151 is a nanomolar antagonist that acts at the melanin-concentrating hormone receptor 1 (MCH1). S38151 is more stable than its purely peptide counterpart, essentially because of the blockade of its N-terminus. Therefore, , its action on various models of obesity was studied. Acute intracerebroventricular (i.c.v.) administration of S38151 in wild-type rats counteracted the effect of the stable precursor of melanin-concentrating hormone (MCH), NEI-MCH, in a dose-dependent manner (from 0.5 to 50 nmol/kg). In genetically obese Zucker fa/fa rats, daily i.c.v. administration of S38151 induced dose-dependent (5, 10, and 20 nmol/kg) inhibition of food intake, water intake, and body weight gain, as well as increased motility (maximal effect observed at 20 nmol/kg). In Zucker fa/fa rats, intraperitoneal injection of S38151 (30 mg/kg) induced complete inhibition of food consumption within 1 h. Daily intraperitoneal injection of S38151 (10 and 30 mg/kg) into genetically obese ob/ob mice or diet-induced obese mice is able to limit body weight gain. Furthermore, S38151 administration (10 and 30 mg/kg) does not affect food intake, water intake, or body weight gain in MCHR1-deleted mice, demonstrating that its effects are linked to its interaction with MCH1. These results validate MCH1 as a target of interest in obesity. S38151 cannot progress to the clinical phase because it is still too poorly stable in vivo.